Effects of profile errors on lubrication performance of helical gears. (July 2017) - Clarke, A.; Jamali, H.U.; Sharif, K.J.; Evans, H.P.; Frazer, R.; Shaw, B.
Abstract: Analysis of the elastohydrodynamic lubrication (EHL) of gears generally assumes that the tooth flanks are smooth surfaces. There is considerable interest in establishing the extent to which smooth surface analyses are distorted by the presence of surface roughness. The current paper concerns a different scale of deviation from the specified surface profile, namely involute profile error. The paper quantifies the deviation from the smooth surface behaviour using standard profile error measurements, and also considers how the means by which profile error is measured influences the outcome/conclusions. Transient EHL analyses of the meshing cycle of helical gears taking profile error data from a gear measuring machine are compared with analyses using equivalent measurements determined by the waviness from surface profilometer measurements. Highlights: Measured profile errors were incorporated into a 3-D EHL point contact model of the meshing cycle of a pair of helical gears. They were found to increase maximum pressure and reduce minimum film thickness. Two methods of measuring profile error were investigated. The results were sensitive to the way in which profile error was measured and filtered.